Hz. Peygamber’e Hakaretin Cezası - (:unkn) unknown (My University, 2018)
Allah dünya ve ahiret saadetine ulaşmaları için insanlara peygamberlergöndermiştir. Peygamberlik zincirinin son halkası Hz. Peygamber’dir. Hz. Peygambergerek yaşadığı dönemde, gerekse vefatından sonra bazı kimseler tarafından hakaretemaruz kalmıştır. Bu çalışmada, Hz. Peygamber’e hakaretin cezası üzerindedurulmuştur. Amacımız İslam hukukunda Hz. Peygamber’e hakaret eden kişiye verilencezayı tespit etmektir.

Allah sent prophets to the people to reach the happiness of the world and hereafter. The last ring of the chain of the prophecy is the Prophet Muhammad. The Prophet has been insulted by some people both in his lifetime and after his death. This study is focusing on the punishment of insulting the Prophet. Our aim is to determine the punishment given to the person who insults the Prophet in Islamic law.
The Punishment for Insulting the Prophet Muhammad
Keywords: Din Bilimi